Entrepreneurship education and the entrepreneurial intentions of students - Mohd. Asraf, Ratnawati; Yusof Khan, Zarinah Jan (American Scientific Publishers, 2017)
This paper describes the results of a qualitative study that sought to discern whether entrepreneurship education has an influence on the intentions of students to be self-employed after graduation. The research used the faceto- face in-depth interview to obtain the students’ perceptions of the entrepreneurship programme and whether it affected their intention to become entrepreneurs. The findings suggest that entrepreneurship education is strongly linked to students’ entrepreneurial intention. © 2017 American Scientific Publishers. All rights reserved.